Effects of Different Processing Methods on the Content of Rutin and Tannin in Sophora japonica Herb Medicine - You, Shanwen; Fu, Yingjie (Serican Journal of Medicine, 2025)
Objective: To investigate the effects of different processing methods on the content of rutin and tannin in Sophora japonica herb medicine (Chinese herb medicine name: Huai Mi or Huai Hua). Methods: Huai Mi was processed with different methods. Tannin content was determined using potassium permanganate titration method. Rutin content was quantified using ultraviolet spectrophotometry. Results: The tannin content was the highest in stir-fried-to-coke samples (1.87%), while the highest rutin content was observed in stir-fried-to-yellow samples (0.134%). The stir-fried-to-ash samples had the lowest contents of both rutin and tannin. Conclusion: Processing methods critically impact the contents of bioactive compounds in Sophora japonica herb medicine. Optimizing these methods may enhance medicinal efficacy and utilization